Sawer: Komunikasi Simbolik pada Adat Tradisi Suku Sunda dalam Upacara Setelah Perkawinan - Pien Supinah (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2006)
Sawer is a symbolic communication expressed on Sundanese wedding tradition. Sawer means spreading wealth like water fountain. This ritual is leading by juru sawer, using properties such as leaves, flowers, grains, and coins. This article explores meanings contained in sawer ritual: rice/grains symbolizes food happiness, sirih leaves symbolizes harmony, yellow color symbolizes golden which means noble, flowers symbolize aromatic smell, and coins symbolizes wealth. From communication perspectives, tradition was perceived as a means of transmitting message. Sawer expressed transcendental communication, relationship with people, and metaphysical communication.